Gender Equality Representation in the Movie Avatar the Last Airbender - M. Ibnu Naufal Maskuri; Angella Dias Paramitha (LP2M UIN Sunan Kalijaga, 2024)
The film industry is often considered as a mere entertainment medium, but the reality is that today's films are a communication medium that contains many representations of real-world life portraits, one of which is the topic of gender equality. Gender equality and the feminist movement have always had a place in the world of film, but there is still a stigma that women who only rely on their appearance or physique will be more dominantly displayed than women with good acting skills in the entertainment world. As the largest animation company in the world, Disney also released a film that also voiced gender equality through the film Avatar the Last Airbender through scenes and Katara characters in the film. The purpose of this study is to determine and understand the representation of the message of gender equality contained in the film Avatar the Last Airbender based on the scalpel approach of Roland Bartes' semiotic theory with 3 elements of meaning, namely denotation, connotation and myth. This study found that in the film Avatar the Last Airbender through dialogues and images there is a message about equality represented by the character Katara both in terms of connotation, denotation and myth. Katara as a female character in the film emphasizes the character of a woman who is brave, intelligent and does not want to be underestimated. Seen through the character of Katara in the scene leading to the practice of voicing and representing the importance of gender equality to be voiced in community life. [Industri perfilman sering dianggap sebagai media hiburan semata, namun realitanya saat ini film merupakan media komunikasi yang memuat banyak representasi potret kehidupan dunia nyata salah satunya topik mengenai kesetaraan gender. Kesetaraan gender dan gerakan feminisme selalu mendapat tempat didunia perfilman namun masih ada stigma bahwa perempuan hanya mengandalkan rupa atau fisik akan lebih dominan sering ditampilkan dibandingkan perempuan yang kemampuan aktingnya baik dalam dunia hiburan. Sebagai perusahaan animasi terbesar di dunia Disney juga merilis film yang ikut menyuarakan mengenai kesetaraan gender melalui film Avatar the Last Airbender melalui adegan-adegan dan tokoh Katara dalam film know know. Tujuan dari penelitian ini adalah untuk mengetahui dan memahami representasi pesan kesetaraan gender yang terdapat pada film Avatar the Last Airbender berdasarkan pendekatan pisau bedah teori semiotika Roland Bartes dengan 3 elemen makna yaitu denotasi, konotasi dan mitos. Penelitian ini menemukan bahwa dalam film Avatar the Last Airbender melalui dialog-dialog serta gambar adanya pesan mengenai kesetaraan yang diwakili oleh tokoh Katara baik secara konotasi, denotasi dan mitos. Katara sebagai tokoh perempuan dalam film menonjolkan karakter perempuan yang berani, cerdas serta tidak ingin dipandang sebelah mata. Terlihat melalui tokoh katara dalam adegan mengarah kepada praktik pada aksi menyuarakan serta merepresentasikan akan pentingnya kesetaraan gender untuk disuarakan dalam kehidupan bermasyarakat.]